PENETAPAN LOKASI DAN AKIBAT HUKUMNYA TERHADAP PEMBAYARAN GANTI KERUGIAN DALAM PENGADAAN TANAH BAGI PEMBANGUNAN UNTUK KEPENTINGAN UMUM - Rosana Dewi Langelo (University Of Bengkulu Law Journal, 2018)
The process of land acquisition for development for wide-ranging public interest is always carried out with the stages as stipulated in Law Number 2 Year 2012 and its implementing regulations. However, other things with the procurement of small-scale land that can be done by way of sale and purchase, exchange or other means agreed by both parties without going through the stages set forth in the laws and regulations implementation. Article 121 of Presidential Regulation No. 148 of 2015 in paragraph (3) states that small-scale land procurement can be carried out without location determination. In the absence of a location stipulation in small-scale land acquisition resulted in agencies requiring land can not consign or take care of damages in court because one of the conditions set forth in Supreme Court Regulation No. 3 of 2016 to do consignment or nursing in court requires determination location set by governor or mayor / regent.